SOME INDICES OF CARDIOHEMODYNAMICS, BLOOD PRESSURE AND ACTIVITY OF TUMOR NECROSE FACTOR-ALPHA IN PATIENTS WITH ESSENTIAL HYPERTENSION AND COMORBID DUODENAL ULCER AT THE STAGE OF EARLY REHABILITATION - Burmak , Yurii; Petrov , Yevhen; Ivanytska, Tetiana; Іvanytskyi Іgor (Collection of scientific papers «ΛΌГOΣ», 2024)
The modern stage of studying the genesis and evolution of essential hypertension (EH) determines the important role of the immune system, namely the activation of cells of innate and adaptive immunity, the mediators of which are directly involved in the development of low-intensity chronic inflammation [1]. Data on the role of mediators of intercellular communication in the mechanisms of development of arterial hypertension and, in particular, tumor necrosis factor-alpha (TNF-α) are being studied and updated.